Nutritional modulation of neuroinflammation in Alzheimer’s disease and mild cognitive impairment: a systematic review of clinical and preclinical evidence - Mahmoud AL Sayed; Ahmed Said; Mohamed Meselhy (BMC Geriatrics, 2026)
Abstract Background Neuroinflammationis a key contributor to the pathogenesis of Alzheimer’s disease (AD) and mild cognitive impairment (MCI). Nutritional interventions have been proposed as potential modulators of neuroinflammatory pathways; however, the consistency and strength of the available evidence remain uncertain. This systematic review evaluated the clinical and preclinical evidence regarding the effects of nutritional interventions on neuroinflammatory mechanisms relevant to AD and MCI. Methods PubMed/MEDLINE, Embase, Scopus, and Web of Science were systematically searched for studies investigating nutritional interventions and neuroinflammatory outcomes. Eligible studies included randomized controlled trials and preclinical experimental investigations evaluating omega-3 fatty acids, ketogenic dietary interventions, B-vitamin supplementation, vitamin D, and microbiota-targeted strategies. Primary outcomes included inflammatory cytokines, neuroinflammatory signaling pathways, oxidative stress biomarkers, and glial activation. Methodological quality and risk of bias were assessed using study design-specific appraisal tools. Results Twenty-two studies met the eligibility criteria, including ten clinical studies and twelve preclinical investigations. Overall, nutritional interventions were associated with modulation of neuroinflammatory biomarkers, including TNF-α, IL-1β, and IL-6, together with alterations in NF-κB and NLRP3 signaling, microglial activation, and oxidative stress pathways. The most consistent evidence supported omega-3 fatty acids and ketogenic dietary interventions, although evidence for ketogenic strategies was derived predominantly from preclinical studies. Evidence for B-vitamin supplementation, vitamin D, and microbiota-targeted interventions was limited because relatively few eligible studies were available. Considerable heterogeneity was observed across intervention protocols, outcome measures, and study populations. Conclusions Nutritional interventions may modulate biological pathways involved in neuroinflammation; however, the strength and certainty of the evidence vary across intervention categories. Larger, well-designed randomized controlled trials incorporating standardized neuroinflammatory biomarkers are required to clarify the therapeutic potential of nutritional strategies for AD and MCI.